Estimating resistive and dielectric effects during microwave heating of Fe0.22Ni0.67Mn2.11O4 - Aguilar Garib, Juan Antonio; García, Felipe; Valdez Nava, Zarel (2009)
Dielectric approaches for estimating microwave heating of ceramics and polymers assuming that resistive effects are small enough to be neglected have been applied quite often. However, these approaches are not valid for semiconductors. Permittivity and resistivity are very sensitive to chemical composition; therefore it is difficult to extrapolate properties from similar materials as can be done with thermal properties. The objective of this work is to estimate the dielectric and resistive contributions during microwave heating, solving the electromagnetic and heat transfer equations by means of Finite Element Method (FEM) using the software ANSYSTM. The experiments were performed over a parallelepiped made of compacted and sintered powders of the manganite, which is a negative thermal coefficient thermistor, placed inside a waveguide and exposed to 2.45 GHz microwaves at different powers. Temperature was taken with sheathed thermocouples that also served as electrodes for monitoring electric resistance. Matching experimental data and simulation results provided values for the properties within acceptable range. An operative model for simulating heating of a sample placed in a waveguide was built, considering either resistive or dielectric effects, which in turn helps to estimate these properties applying it jointly with the experimental technique shown.